RENAL INVOLVEMENT IN JUVENILE IDIOPATHIC ARTHRITIS - Karimdzhanov I.A; Madaminova M.Sh (Scholar Express Journals, 2023)
Juvenile idiopathic arthritis (JIA) is systemic diseases that can involve various organs, including the kidneys. JIA can exhibit characteristic renal involvement, which requires proper treatment and diagnosis. In this review, we discuss renal involvement in classic JIA. Renal manifestations in JIA vary from asymptomatic to end-stage kidney disease. It is important to recognize that renal abnormalities can be a symptom of rheumatologic disease because they can provide important signals towards establishing a personalized treatment plan.
Keywords: Arthritis; juvenile; kidney diseases; children